The influence of tailings concentration and waste rock medium length on horizontal seepage deformation - Sheng, Mingqiang; Ouyang, Min; Xu, Jiayu; Wang, Sijun; Lei, Zhicong; Liu, Xinxin (Frontiers in Earth Science, 2025)
The technique of storing tailings with a waste rock embankment network integrates the high waste dumping site and high tailings pond engineering into one, effectively reducing the construction footprint. However, the significant particle size difference between waste rock and tailings often leads to seepage damage. Therefore, understanding the development mechanism of seepage deformation in tailings stored with waste rock embankment networks is crucial. This study examines the influence of different slurry concentrations (5% and 10%) and waste rock media lengths (30 cm, 60 cm, and 90 cm) on the infiltration and deformation of tailings within a waste rock medium. A specially designed infiltration test device was employed to simulate the process, and a three-dimensional visual dynamic microscopic simulation of tailings transport in waste rock was performed using a computational fluid dynamics-discrete element method (CFD-DEM) coupling. The study investigated the contact loss mechanism of tailings in the waste rock medium and the particle transport behavior through a combination of macroscopic and microscopic analyses. Results indicate that at 600 s, with a 60 cm media length, the filtration rates for 5% and 10% slurry concentrations were 15.2% and 6.6%, respectively. For a 10% concentration slurry at 600 s, the filtration rates for 30 cm, 60 cm, and 90 cm media lengths were 4.2%, 6.6%, and 15.9%, respectively. The experimental and numerical simulation results demonstrate that higher tailings concentrations lead to a higher likelihood of clogging in the waste rock medium, reducing the cumulative filtrate mass. The filtration rate initially rises sharply, peaks, and then decreases rapidly before stabilizing. Moreover, shorter waste rock media lengths result in earlier filtration onset, lower peak filtration rates, and lower stable filtration rates in the later stage. These findings provide valuable references for the future engineering design of tailings ponds utilizing waste rock embankments.